PROSES PEMBUATAN PLATE HOOK FUEL LID MENGGUNAKAN MESIN STAMPING PRESS - Sudiana, Jajang; Rachmat, Asep (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
When starting to do practical work at PT Persada Selaras Indonesia several problems were found, one of which was why the SPHC-PO material was used in the production of Plate Hook Fuel Lid and how the production process was used Stamping Sheet Metal Press in the production process using the Blanking and Bending processes Based on the process of making the Plate Hook Fuel Lid, this practical work has the goal of knowing the working process of the Stamping Press machine. The methods used in this practical work are the process of observing, summarizing and recording data from sources and hard copies from PT. Persada Selaras Indonesia After carrying out the methods systematically obtained several results from practical work, including being able to make a product using a Stamping Press machine and recognizing the flow of the production process in the automotive part industry